A computational study on the steric effects of naphthenic moieties on aggregation interactions of nonconventional petroleum constituents1. (20th July 2014) - Seidl, Peter R.; Oliveira, Jackeline S. C.; da Costa, Leonardo M.; Stoyanov, Stanislav R.; Johnson, Richard; Tor, Yitzhak; Siegel, Jay
<x xml:space="preserve">Abstract</x> Nonconventional oil is usually heavy and extra heavy crude or light oil that is relatively unstable. This oil contains varying proportions of larger, more aromatic constituents rather than molecules that can be distilled directly into fuels and petrochemicals. We perform density functional theory (ωB97X‐D/6‐31G(d, p)) calculations to study the contributions of steric effects and dispersion interactions in a series of dimers and trimers of model hydrocarbons containing fused aromatic and cyclohexyl (referred to in the petroleum literature as naphthenic) rings. The aggregation behavior of these molecules is analyzed in terms of the optimized geometry, atomic charges, interaction enthalpy (∆H), and Gibbs free energy (∆G298). The ∆H and ∆G298 values show that all the dimerization and trimerization processes are exothermic, and only a few are spontaneous at 298 K. The naphthenic hydrogen atoms have a key role in the orientation of the monomers in dimer and trimer aggregates. The interaction among naphthenic hydrogen atoms belonging to adjacent monomers causes steric repulsion. The interaction of naphthenic hydrogen atoms with the π‐electronic clouds of aromatic rings in adjacent molecules causes attraction. In both cases, the naphthenic hydrogen atoms cause deviation of the monomer from the initial parallel displaced configuration in dimers and trimers. These results reflect the importance of naphthenic rings and their steric interactions in determining the relationship between structures of nonconventional petroleum constituents and their tendency to aggregate and cause fouling. Copyright © 2014 John Wiley & Sons, Ltd.